ANALISIS KESALAHAN PESERTA DIDIK DALAM MENGERJAKAN SOAL MATERI BRSD DITINJAU DARI KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DAN SELF REGULATED LEARNING - Sheilla Zalzabilla Al-Jabar; Risma Amelia; Eva Dwi Minarti (IKIP Siliwangi, 2023)
The purpose of this research is to analyze students' mistakes when working on material problems on flat sided geometric shapes in terms of mathematical problem solving abilities and self-regulated learning. The method used in this research is descriptive analysis method. The data collection technique was taken by giving questions about the mathematical problem-solving ability of the flat-sided geometric material to students and a non-test instrument in the form of a self-regulated learning questionnaire. This research was conducted on 23 students at SMP Negeri 5 Cipongkor, class IX. The results of the study showed that there were students' errors in working on BRSD material questions based on indicators of mathematical problem solving ability; 1) identify the elements that are known, asked, and the adequacy of the required elements, 2) formulate mathematical problems or develop mathematical models, 3) apply strategies to solve various problems within or outside mathematics, 4) explain or interpret the results according to the initial problems, 5) use mathematics meaningfully.